Bastardierungen innerhalb des Artenkomplexes um die Grünstreifige Kartoffelblattlaus Macrosiphum euphorbiae (Thomas). - Möller, Friedrich Wilhelm (Contributions to Entomology = Beiträge zur Entomologie, 1971)
Reciprocally achieved hybridizations of Macrosiphum euphorbiae (Thomas) with M. stellariae Theobald and M. gei (Koch) respectively, and of M. stellariae x M. gei produced viable parthenogenetic hybrid polulations which finished their annual cycle exclusively by oviparous females. However, all attempts to hybridize M. cholodkovskyi (Mordvilko) which any of the other three Macrosiphum species completely failed. The sexuals scarcely noted one another thus demonstrating prezygous isolation, which is additionally strengthened because M. cholodkovskyi is segregated through its host plant which is refesed by the other three Macrosiphum species under consideration. ...